Macular Bruch membrane holes in highly myopic patchy chorioretinal atrophy - Ohno-Matsui, Kyoko; Jonas, Jost B.; Spaide, Richard F. (American journal of ophthalmology, 2016)
Purpose - Patchy atrophy is a type of chorioretinal atrophy located outside of the fovea in eyes with myopic retinopathy. Bruch membrane defects have previously been described to occur in highly myopic eyes in foveal chorioretinal atrophy associated with choroidal neovascularization (CNV). We examined whether Bruch membrane defects can be found also in patchy atrophy. - Design - Retrospective observational case series. - Methods - The study included all patients who were consecutively examined for high axial myopia (axial length ≥26.5 mm) and patchy atrophy in the study period from September to November 2015. The patients underwent a comprehensive ophthalmologic examination including swept-source optical coherence tomography (OCT) of the macula. Main outcome measures were macular Bruch membrane defects. - Results - Out of 22 eyes (17 patients) with patchy atrophy, 21 eyes (96%) showed macular Bruch membrane defects, which were characterized by a lack of Bruch membrane, retinal pigment epithelium (RPE), photoreceptors, and choriocapillaris. At the edges of the macular Bruch membrane defects, the ends of the Bruch membrane were folded and the RPE was upturned. The inner retina overlying the area of the Bruch membrane defect was markedly thinned. - Conclusions - Macular Bruch membrane defects belong to the hallmarks of a type of myopic chorioretinal atrophy not associated with CNV (ie, patchy atrophy). Considering that Bruch membrane defects were also observed in myopic CNV-related foveal atrophy, macular Bruch membrane defect might be a common finding in fundus lesions related to pathologic myopia.
Gesehen am 25.06.2019